From Design to Implementation: Addressing the Causes of Violent Conflict in Nigeria. Issue 1 (2nd January 2014) - El-Bushra, Judy; Ladbury, Sarah; Ukiwo, Ukoha
This article considers the ways in which knowledge and research influenced the design of a programme to reduce violent conflict in Nigeria. The diversity of sources and forms of conflict in Nigeria, and the way that local grievances interact with national struggles over politics and resources, combined with a need to show measurable results within five years, made the task of programme design extremely challenging. The article discusses how the project design team responded to this challenge. It describes the four main lessons that emerged from dialogue-based research studies that helped the design team formulate a theory of change for the programme, and subsequently its methodological approach and activities. The studies shaped the central theme of the project, which was the need to transform conflict management institutions into genuinely inclusive forums for dialogue, thereby regaining the trust of those currently excluded from dialogue but yet most affected by violence – particularly unemployed youth and women and girls. The article does not portray research and knowledge simplistically, as the sole solution to project design issues. Rather, it shows that if research findings can take designers directly to the core of the problems as perceived by those most affected by them, then they can play a critical role in designing appropriate interventions and, as implementation proceeds, to demonstrating progress towards project goals.